PERFORMA PEMIMPIN PEREMPUAN DI PARLEMEN - Anis Endang SM; Adinda Tessa Naumi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
This research aims to seekthe performance of women leaders in the Regional House of Representativesof Bengkulu City in communicating politics and representing themselves as leaders in a